Proposta de um modelo para aplicar a gestão de riscos incremental em projetos na área de tecnologia de informação - Damaceno, Vanessa Macedo (Universidade do Vale do Rio dos Sinos, 2020)
: Inserted in an increasingly competitive and extremely complex context, the technology companies in general are looking for continuous improvement of their processes and results, combined with the reduction of unnecessary costs arising from the lack of risk management of projects for which they are contracted. Research this assertiveness in the expected results or the great challenge that everyone faces and is reached through maturity and recognition of the benefits that risk management brings to a company. Be consistent with your customers' expectations and carry out management on the next delivery, keeping possible deviations from planning under monitoring and control that they can do. In recent years, we have been able to observe the rise of the application of SCRUM methods in software development projects, where interactive / incremental cycles with program updates that add value to the customer and communication are the pillars of this structure. The risk management process, despite bringing proven benefits, is still seen as a heavy and complex procedure by companies and project teams, the objective of this study is to combine the dynamics of agile methods with the risk management process of the management model cascade projects, developing a model proposal to apply incremental risk management to projects in the area of information technology.
Keywords: Riscos; Gestão de projetos; Modelo incremental; Banco de riscos; Risks; Project management; Incremental model; Risk bank